Necesidad de regular en el código del trabajo, la modalidad de la jornada laboral de 21 días de trabajo y 7 de descanso. - Franco Alcívar, Mayra Narcisa (2014)
The working according to our Code states that it is eight hours per day and forty per week for every person employed persons, ie it is under a dependency of another person becomes the employer; but it is true that work on the ground is six hours per day and only by way of extraordinary overtime or recovery may be extended an additional hour with adequate remuneration and their respective charges. Speaking the maximum workday is eight hours a day you should also understand that it is not prohibited from entering a day for less hours of work, as may be provided in a collective agreement. The Labour Code and the conference breaks is regulated, but the fact is that oil, the tasks performed in remote locations, twenty consecutive working days, having a descaso seven days, that contrary to the mandatory breaks that workers should have Saturdays and Sundays, and that is five hours a week. This type of work is not covered by the Labour Code, this code is very clear that a person should work more than five consecutive days and two, or Saturday and Sunday from furlough. Look to the Labour Code is that the person does not suffer from work-related fatigue and accidents are reduced. These modalities work 21 x7, are not regulated in the Labour Code, for such circumstances must normarse in this legal body, the most appropriate mode of employment in these sectors of production, and is set on Sunday to furlough, to thereby no constitutional rights of workers are violated. The type of contract to 21 x 7 that are signed between a worker and the firm and not be regulated in the Labour Code, is opposed to the merits of the substantive law by which rights and duties are developed, creating legal uncertainty for public institutions and private. As legal disadvantages day 21/7 to workers is not regulated, is involved in a different way, and so that in itself should not exist only a few privileges be regulated by law and the other has lower profit a smaller percentage discrimination is generated, this relates to the previous one because it is a result of marginalization, and that means legal problems within the legal and social reality that our society is undergoing